2022
DOI: 10.1002/adsc.202201095
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Enhanced C−H Amination of Cyclic Ethers with Iminoiodinanes

Abstract: A two‐step protocol allowing the C−H amination of cyclic ethers with iminoiodinanes, followed by the reduction of the resulting intermediate has been developed for the preparation of amino alcohols. The initial C−H functionalization is accelerated by visible light, improving the reactivity compared to the thermal process performed in the dark. The effect of different substituents on the photochemical reactivity of iminoiodinanes has been studied both experimentally and computationally. Photophysical measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Lately, Jurberg and König reported a two-step protocol allowing the C(sp 3 )-H amination of cyclic ethers with iodonium imides, followed by the reduction of the resulting intermediate (Scheme 11E). 58 The amino alcohol products have been obtained in good yields under photochemical or thermal conditions. In many examples it was found that light has a beneficial effect on the reaction yield.…”
Section: Reactions Of Iodonium Imidesmentioning
confidence: 99%
“…Lately, Jurberg and König reported a two-step protocol allowing the C(sp 3 )-H amination of cyclic ethers with iodonium imides, followed by the reduction of the resulting intermediate (Scheme 11E). 58 The amino alcohol products have been obtained in good yields under photochemical or thermal conditions. In many examples it was found that light has a beneficial effect on the reaction yield.…”
Section: Reactions Of Iodonium Imidesmentioning
confidence: 99%
“…In this context, examples of representative classes of organic molecules undergoing mild photolysis include acylsilanes, 5 pyridotriazoles, 6 dithiocarbonates, 7 hypervalent iodine compounds, 8 phosphonium salts, 9 organometallic complexes, 10 and diazo compounds. 11 Remarkably, the number of different classes of organic molecules recognized to directly undergo photolysis under visible light irradiation was quite limited until recently, but in the last decade has become significantly more important.…”
Section: Introductionmentioning
confidence: 99%
“…11 Remarkably, the number of different classes of organic molecules recognized to directly undergo photolysis under visible light irradiation was quite limited until recently, but in the last decade has become significantly more important. 5–11…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an environmentally benign, green, and mild approach is highly desirable for C–N bond construction, which can afford densely substituted C2-aminated naphthoquinones and quinones. In recent decades, visible-light-driven photocatalyzed strategies have been developed, serving as a mild and powerful tool for carbon–carbon, carbon–heteroatom, and particularly C–N coupling reactions. In 2016, MacMillan and co-workers reported photocatalyzed aryl amination using ligand-free Ni salt. The visible-light-mediated C 2 -amination of thiophenes with engineered amine substrates by using DDQ as an organo-photocatalyst has been achieved recently by Lei and co-workers .…”
Section: Introductionmentioning
confidence: 99%